The Effectiveness of Audio- Lingual Method on Students Pronunciation Performance - Muhammad Fadiil Abrar; Sayid Ma’rifatulloh (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to determine the effectiveness of Audio-Lingual Method (ALM) on students' pronunciation performance. Proper pronunciation is one of the important aspects in foreign language learning, especially English, which is often a challenge for students. This study was conducted using a quasi-experimental design, in which two different groups of students were given different treatments: one group was given instruction using the Audio-Lingual method, while the other group was given the conventional method. Data was collected through pronunciation tests conducted before and after the intervention. The results showed a significant improvement in the pronunciation performance of students who received treatment with the Audio-Lingual method compared to the control group. The findings support the hypothesis that the Audio-Lingual method is effective in improving students' pronunciation skills. This study makes an important contribution to language teaching, particularly in improving students' pronunciation skills through a more structured and repetitive approach.